2017
DOI: 10.1002/adfm.201605196
|View full text |Cite
|
Sign up to set email alerts
|

Nanoscale Defect Engineering and the Resulting Effects on Domain Wall Dynamics in Ferroelectric Thin Films

Abstract: Defect engineering is one of the cornerstones of the modern electronics industry. Almost all electronic devices include materials that have been doped by ion bombardment. For materials where crystallinity is essential, such as ferroelectrics, defect type and concentration can vastly influence properties and are often used to optimize device performance. This study shows a method to effectively control the density and position on the nanoscale of defect sites in thin films of Pb(Zr,Ti)O3 via focused ion beam mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 36 publications
2
21
0
Order By: Relevance
“…The first one relies on the study of individual domain wall movement on long-time scales. It describes the nucleation and growth of domains and their interaction with defects, interfaces and existing domain walls [18][19][20] . The second one aims to understand collective movements during short-time scales 21,22 .…”
mentioning
confidence: 99%
“…The first one relies on the study of individual domain wall movement on long-time scales. It describes the nucleation and growth of domains and their interaction with defects, interfaces and existing domain walls [18][19][20] . The second one aims to understand collective movements during short-time scales 21,22 .…”
mentioning
confidence: 99%
“…This paucity of knowledge regarding the role of intrinsic point defects is primarily related to difficulties in on-demand and controlled production of such defects, which are typically formed during the synthesis process with their concentration and type being dictated by the laws of thermodynamics [12]. Recent studies on complex-oxide thin films have, however, shown that energetic ion beams are effective for ex post facto production of intrinsic point defects with control over their type, concentration, and location [13][14][15][16][17][18][19][20]. This controlled defect production provides opportunities for the systematic study of defectproperty relations in relaxors.…”
mentioning
confidence: 99%
“…S1(a) [21]). The total initial concentration of induced defects is calculated to vary from ∼10 18 to ∼10 20 cm −3 , for the ion-dose range used. It is important to note that the helium ions are implanted at a depth of ∼14.5 μm within the NdScO 3 substrate (Supplemental Material, Fig.…”
mentioning
confidence: 99%
“…The dynamical behaviour of domain walls is subject to intense research because it is at the core of ferroelectric switching [197][198][199][200] . One approach relies on the study of individual domain wall movement on long-time scales.…”
Section: Box 2 | Domain Wall Dynamics: Avalanches In Ferroelectricsmentioning
confidence: 99%